(untitled) (Journal of Partial Differential Equations, 2015)
" In this paper,we find two auxiliary functions andmake use of themaximum principle to study the level sets of harmonic function defined on a convex ring with homogeneous Dirichlet boundary conditions in mathbbR^2. In higher dimensions, we also have a similar result to Jagy's."